IoT and its business impact on remote monitoring of patients with chronic diseases in Germany - Horvath, Anna-Sophia (2020)
The goal of this dissertation is to determine the business impact of IoT and remote monitoring on patients with chronic diseases in Germany. Therefore, expert interviews with representatives of the four major affected stakeholder groups were conducted. These four groups consist of statutory health insurance companies, businesses, doctors and patients. The aim of these interviews was to assess the current status of IoT and remote monitoring in the German healthcare system and to find out about the main obstacles that currently keep the business impact at a low level. Although only representatives from the first three groups could be interviewed all interviewees agreed that IoT is in its early stages in Germany. The main obstacles impeding a significant growth of IoT and remote monitoring in Germany are identified as technological, regulatory, and cultural ones. Additionally, the self-governing structures of the German healthcare system and the multidisciplinary approach of already ongoing IoT projects complicate the diffusion of IoT solutions. Despite these barriers the interviewed experts are convinced that IoT and remote monitoring will prevail in Germany sooner or later.